Effect of chemical and time of cutting of milked yam Minisetts on storability and Performance of Minisetts (Journal of Science and Technology, 2016)
The milked yam minisett technology was developed as a rapid method of seed yam multiplication with an advantage of higher, early and uniform sprouting of setts compared to the normal minisett technology. A study was carried out at the Teaching and Research Farm as well as AgronomyProcessing and Storage house of the University of Agriculture, Makurdi to test the effect of chemicals and time of cutting of milked yam minisetts on storability and performance of setts in the field. The setts were milked in September and October 2006 and same time in 2007, treated with chemicals and reburied. They were harvested in December and stored for 5 months before planting them out in the field. Results showed that setts milked and cut on October 30 each year recorded the greatest rotting of setts in the month of May of the following year before plantingthem out in the field, followed by setts milked and cut on September 30. The setts milked and cut on October 15 each year, stored better than the others and had the highest percentage germination in storage. The best treatment among setts milked and cut on September 30 (Monceren)yielded more than the best treatment among setts cut on October 15 (Monceren and rizolex) by about 73.6% and the best treatment cut on October 30 (Monceren) by about 194.6%. Also the best treatment among setts milked and cut on October 15 yielded more than the best treatmentamong setts milked and cut on October 30 by about 69.7%. So in terms of the storability of setts, the setts milked and cut on October 15 were the best while setts milked and cut on September 30 that survived storage performed best in the field. The best time to milk and cut the setts is between the end of September and mid October. Monceren fungicide performed better than all the other chemicals.